Adab Murid Terhadap Guru Dalam Perspektif Pendidikan Islam Studi Kasus Di Sekolah Al-Ittihadiyah Medan - Hasanuddin, Hasanuddin; Pasaribu, Munawir (EL-EMIR Institute, 2025)
This article examines the importance of students' manners toward teachers from the perspective of Islamic education, which has recently been seen as declining. The purpose of this research is to provide students with an understanding that manners are more important than knowledge. This research method uses a descriptive qualitative approach in the form of a literature study, examining books, classical texts, and the contents of the Quran related to this discussion. The results found that manners encompass not only external respect but also reflect internal attitudes that influence the formation of students' character, spirituality, and intellect. Based on an analysis of Surah Al-Kahf (verses 65-70), several important principles are explained, such as respect, patience, asking permission from the teacher, acknowledging the teacher's knowledge, being serious in learning, and avoiding negative prejudice. These principles are relevant in modern education to create harmonious relationships between students and teachers, thus supporting an effective and meaningful learning process. This research highlights that manners toward teachers serve not only as a form of etiquette but also as a way to maintain noble values ​​in facing the challenges of the times.